1994
DOI: 10.1172/jci117273
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of the hydrophobic components of porcine lung surfactant to oxidant stress alters surface tension properties.

Abstract: We have tested the hypothesis that oxidation of lung surfactant results in loss ofsurface tension lowering function. Porcine lung surfactant was exposed to conditions known to cause lipid peroxidation (0.2 mM FeCl2 + 0.1 mM H202 or 5 ,uM CuC12). Lipid peroxidation was verified by detection of conjugated dienes, thiobarbituric acid reactive substances, fluorescent products, hydroxy alkenals, and loss of unsaturated fatty acids. Exposed samples had significantly diminished surface tension lowering ability in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 37 publications
5
39
0
Order By: Relevance
“…Air pollutants have also been recognized to influence the structure and function of the lung surfactant system (6,7). Oxidative inactivation of surfactant by cellular reactive oxygen species (ROS), leading to surfactant lipid peroxidation, protein carbonylation, and functional impairment of surfactant protein A, are thought to be possible mechanisms underlying air pollutantinduced surfactant damage (7)(8)(9)(10)(11). Oxidative damage to lung epithelial cells is a component of acute lung injury and associated respiratory failure (12).…”
mentioning
confidence: 99%
“…Air pollutants have also been recognized to influence the structure and function of the lung surfactant system (6,7). Oxidative inactivation of surfactant by cellular reactive oxygen species (ROS), leading to surfactant lipid peroxidation, protein carbonylation, and functional impairment of surfactant protein A, are thought to be possible mechanisms underlying air pollutantinduced surfactant damage (7)(8)(9)(10)(11). Oxidative damage to lung epithelial cells is a component of acute lung injury and associated respiratory failure (12).…”
mentioning
confidence: 99%
“…This loss of alveolar surfactant is due to several factors including the presence of plasma proteins [13], cleavage of phospholipids by serum phospholipases [14], formation of free radical species (including nitrates, lipid peroxidation, etc.) [15][16][17], and conversion to nonfunctional surfactant with more phospholipid aggregates [14].…”
mentioning
confidence: 99%
“…Exosurf1 is an exogenous surfactant that does not contain apoproteins and this can affect the onset of action and be inhibited by serum proteins. The study by GREGORY et al [19] used a bovine surfactant that contains two apoprotein constituents, whereas the synthetic preparation contains neither protein nor peptides and needs to achieve an in vitro critical concentration in order to exert its effects [16]. These data suggest that for an exogenous surfactant preparation to be effective, it must contain apoproteins.…”
mentioning
confidence: 99%
“…One hallmark of ARDS is the intense inflammation detected in the lung as evidenced by the dramatic increase in the number of PMN that are present in histologic sections or recovered in lavage fluid from patients (7). The release of neutrophil-derived proteases and reactive oxygen intermediates (ROI) has also been implicated in disease pathogenesis, and a number of observations have suggested that these inflammatory products may modify structure or function of lung surfactant (8,9).…”
Section: Introductionmentioning
confidence: 99%